MICROFOSSILS FROM THE RIPHEAN HYPOSTRATOTYPE OF SIBERIA (THE OMAKHTA, KANDYK, AND UST'-KIRBA MICROBIOTAS) - Veis A.F.; Vorob'eva N.G. (My University, 2002)
Organic-walled microfossils from the Riphean hypostratotype of Siberia (the Uchur-Maya region), which represent the Early Riphean Uchur (Omakhta) and Late Riphean Ui (Kandyk and Ust'-Kirba) microbiotas, are considered. The analyzed original materials (over 90 samples) show that the Omakhta microbiota is dominated by small to medium-sized Leiosphaeridia, Myxococcoides, Eomycetopsis, Leiotrichoides, Oscillatoriopsis, and other transit taxa (more than 20 genera and 30 species). New localities, which have been discovered, broaden our knowledge on the microfossil-bearing Omakhta deposits (18 microphytological levels in seven outcrops contrary to the five levels previously known at three sites). These levels are lacking large morphotypes of complex structure, which are present in other regions, the Early Riphean age of deposits is implied by isotopic-geochronological data. The microphytological characteristics of the Upper Riphean Kandyk-Ust'-Kirba interval of the hypostratotype is based on the analysis of 120 collected samples and published data. Microbiotas were found in eight microphytological levels of ten localities (versus six levels of eight sites known before). Forms dominant most representative microbiotas are Chuaria, Simia, Valeria, Cucumiforma, Trachytrichoides, Polytrichoides, Arctacellularia, Palaeolyngbya, and simple forms inherited from the underlying deposits. In addition, some levels of the Ui deposits contain Trachyhystrichosphaera, Prolatoforma, Asperatofilum, Recta, Germinosphaera, Caudosphaera, and some other morphotypes. Relationships between the Omakhta and Ui microbiotas and their comparison with other Riphean microfossil assemblages from Siberian and South Uralian type sections are considered.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей